Yad Vashem, the World Holocaust Remembrance Center - Video Testimonies Resource Center
Throughout our website the voices of the survivors infuse our online exhibitions, historical narratives, teaching units and ceremonies with content and with meaning. We have gathered many of those testimonies in this section where they can be easily accessed by either topic or location, according to the birthplaces of the survivors